2011
DOI: 10.1029/2010rs004584
|View full text |Cite
|
Sign up to set email alerts
|

Comparative testing of four ionospheric models driven with GPS measurements

Abstract: In the context of the European Space Agency/European Space Operations Centre funded Study “GNSS Contribution to Next Generation Global Ionospheric Monitoring,” four ionospheric models based on GNSS data (the Electron Density Assimilative Model, EDAM; the Ionosphere Monitoring Facility, IONMON v2; the Tomographic Ionosphere model, TOMION; and the Neustrelitz TEC Models, NTCM) have been run using a controlled set of input data. Each model output has been tested against differential slant TEC (dSTEC) truth data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…Previous studies (e.g. Angling and Jackson-Booth, 2011;Feltens et al, 2011) have shown that EDAM can accurately represent the ionosphere using GNSS data.…”
Section: The Electron Density Assimilative Model (Edam)mentioning
confidence: 99%
“…Previous studies (e.g. Angling and Jackson-Booth, 2011;Feltens et al, 2011) have shown that EDAM can accurately represent the ionosphere using GNSS data.…”
Section: The Electron Density Assimilative Model (Edam)mentioning
confidence: 99%
“…Such directly observed dSTEC value is typically more accurate than 0.1 TECU (the measurement -thermal noise and multipath-error) and independent of any assumption or model (see more details in [6]). In this sense, dSTEC provides an excellent electron content reference in the (slant) transmitterreceiver line-of-sight, very useful to assess and compare the performance of different ionospheric models.…”
Section: Dstec-gps Assessmentmentioning
confidence: 99%
“…Several geoeffective solar flares occurred from days 70 to 76, 2015 (11 to 17 March), prior to the St. Patrick's Day storm, and these were detected and notified in real time by the MONITOR system by means of the GNSS solar flare indicator, (GSFLAI; Hernández-Pajares et al, 2012;MonteMoreno and Hernández-Pajares, 2014;Singh et al, 2015) and the sunlit ionosphere sudden TEC enhancement detector (SISTED; García-Rigo, 2012). Figures 18 and 19 show the corresponding plots for the days surrounding the St. Patrick's Day storm.…”
Section: Solar Flaresmentioning
confidence: 99%
“…In order to evaluate the proposed ingestion-assimilation method, two different key indicators were considered: the differential slant GPS TEC (dSTEC; as defined for instance by Feltens et al, 2011) and slant GPS TEC calibrated with the UQRG GIMs (STEC). To perform this test, specific MONITOR products (externally provided or derived from internal processors) were used.…”
Section: The Architecture Of the Projectmentioning
confidence: 99%